Traditional Chinese Herbal Medicines for Treating HIV Infections and AIDS - Zou, Wen (Hindawi Publishing Corporation, 2012)
To assess the effects of TCHM on patients with HIV infection and AIDS, we reviewed eleven randomized placebo-controlled trials involving 998 patients. Due to the limited number of RCTs for included trials and the small sample size of each study, we are not able to draw firm conclusions concerning TCHM therapy in treating patients with HIV infection and AIDS. However, some high-quality clinical studies do exist. Studies of diarrhea and oral candidiasis, which are challenging symptoms of AIDS, were demonstrated to have positive effects. Study of peripheral leukocytes, which are a side effect of antiretroviral drugs, suggested that an integrated treatment approach may be of benefit. The overall methodological quality of the trials was adequate; however, randomization methods should be clearly described and fully reported in these trials according to the Consolidated Standards of Reporting Trials (CONSORT).